2019
DOI: 10.1111/desc.12918
|View full text |Cite
|
Sign up to set email alerts
|

Common mechanisms of executive attention underlie executive function and effortful control in children

Abstract: Executive Function (EF) and Effortful Control (EC) have traditionally been viewed as distinct constructs related to cognition and temperament during development. More recently, EF and EC have been implicated in top‐down self‐regulation ‐ the goal‐directed control of cognition, emotion, and behavior. We propose that executive attention, a limited‐capacity attentional resource subserving goal‐directed cognition and behavior, is the common cognitive mechanism underlying the self‐regulatory capacities captured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 165 publications
(308 reference statements)
2
34
0
Order By: Relevance
“…A bifactor model of these EATQ-R EC subscales in a large combined adolescent sample found common EC and an activation-control specific factors (the common EC factor fully accounted for the attentional control and inhibitory control items; Snyder, Gulley, et al, 2015). This structure replicated in a hold-out sample (Snyder, Gulley, et al, 2015) and an independent study (Tiego et al, 2020), and the factors were related to multiple life outcomes (common EC-related negative emotionality, depression and anxiety symptoms, antisocial behavior, and grades, activation control-specific related to negative emotionality, fear, and harm avoidance; Snyder, Gulley, et al, 2015).…”
Section: Ef/ec Questionnairesmentioning
confidence: 69%
See 1 more Smart Citation
“…A bifactor model of these EATQ-R EC subscales in a large combined adolescent sample found common EC and an activation-control specific factors (the common EC factor fully accounted for the attentional control and inhibitory control items; Snyder, Gulley, et al, 2015). This structure replicated in a hold-out sample (Snyder, Gulley, et al, 2015) and an independent study (Tiego et al, 2020), and the factors were related to multiple life outcomes (common EC-related negative emotionality, depression and anxiety symptoms, antisocial behavior, and grades, activation control-specific related to negative emotionality, fear, and harm avoidance; Snyder, Gulley, et al, 2015).…”
Section: Ef/ec Questionnairesmentioning
confidence: 69%
“…Although the EATQ-R and BRIEF use different terminology (EC vs. EF), they have overlapping content, asking about many of the same behaviors (e.g., Behavior Rating Inventory of Executive Function–Self-Report [BRIEF-SR] “I have trouble changing from one activity to another” and EATQ-R “I find it hard to shift gears when I go from one class to another at school,” BRIEF-SR “I forget what I’m doing in the middle of things” and EATQ-R “I tend to get in the middle of one thing, then go off and do something else,” etc.). Of note however, correlations between these questionnaires have not been reported in the literature, with the exception of one study finding a very strong correlation between parent-report BRIEF and EATQ-R EC factors in children, such that they appeared to measure the same construct (Tiego et al, 2020). Thus, there is some preliminary evidence that questionnaire measures of cognitive control, whether conceptualized as EF or EC, measure the same construct.…”
Section: Ef/ec Questionnairesmentioning
confidence: 95%
“…At least in adolescents, Zorza et al [83] argued that EF and EC share some elements, but do not completely overlap. In preadolescents, Tiego et al [90] found that behavioral ratings of EF and EC measured the same self-regulation construct. However, based on assessments at age 4 years, Backer-Grondahl et al ([8] p. 2) argued that EF and EC are "not completely synonymous".…”
Section: Key Concepts and Processes In General Self-regulationmentioning
confidence: 99%
“…Among the frontal sub-regions we assessed, the superior frontal gyrus, the orbitofrontal gyrus, the middle frontal gyrus, and the inferior frontal gyrus are involved in the executive attention network. The executive attention network is primarily responsible for error detection and the goal-directed control of attention and behavior associated with novelty and interference (81,82). This network is active when a conflict is present and inhibitory attentional processes are necessary (81,83).…”
Section: Discussionmentioning
confidence: 99%